2018
DOI: 10.1111/jdi.12838
|View full text |Cite
|
Sign up to set email alerts
|

Lactation and progression to type 2 diabetes in patients with gestational diabetes mellitus: A systematic review and meta‐analysis of cohort studies

Abstract: Aims/IntroductionTo explore the association between lactation and type 2 diabetes incidence in women with prior gestational diabetes.Materials and MethodsWe searched PubMed, Embase and the Cochrane Library for cohort studies published through 12 June 2017 that evaluated the effect of lactation on the development of type 2 diabetes in women with prior gestational diabetes. A random effects model was used to estimate relative risks (RRs) with 95% confidence intervals (CIs).ResultsA total of 13 cohort studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 57 publications
0
34
1
Order By: Relevance
“…Recently published meta-analyses have reported positive effects of long-term breastfeeding of any intensity to reduce diabetes risk in women with a history of GDM [ 35 , 36 ]. In addition, Feng et al (2018) evaluated 13 observational studies and compared the effect of lactation with that of no lactation on diabetes risk reduction; they found a significant diabetes risk reduction in the lactation group [ 55 ]. The authors reported that exclusive lactation for more than six weeks and up to nine weeks postpartum showed an association with a lower risk of T2DM compared to exclusive formula feeding [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published meta-analyses have reported positive effects of long-term breastfeeding of any intensity to reduce diabetes risk in women with a history of GDM [ 35 , 36 ]. In addition, Feng et al (2018) evaluated 13 observational studies and compared the effect of lactation with that of no lactation on diabetes risk reduction; they found a significant diabetes risk reduction in the lactation group [ 55 ]. The authors reported that exclusive lactation for more than six weeks and up to nine weeks postpartum showed an association with a lower risk of T2DM compared to exclusive formula feeding [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Feng et al (2018) evaluated 13 observational studies and compared the effect of lactation with that of no lactation on diabetes risk reduction; they found a significant diabetes risk reduction in the lactation group [ 55 ]. The authors reported that exclusive lactation for more than six weeks and up to nine weeks postpartum showed an association with a lower risk of T2DM compared to exclusive formula feeding [ 55 ]. Still, the meta-analyses reported by Tanase-Nakao et al (2017) and Feng et al (2018) lacked prospective data of cohorts with long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is also less in breastfeeding mothers; on average, obese mothers who breastfed are 8 kg lighter six years after delivery compared to mothers who had not breastfed their infants [ 31 ]. Type 2 diabetes, hypertension, and hyperlipidaemia are also less, although these effects could, at least in part, result from reductions in obesity rates [ 32 , 33 ]. A large meta-analysis of cohort studies reported an approximately 30% significantly lower risk of maternal type 2 diabetes comparing mothers with the longest duration of breastfeeding versus those the shortest duration [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) refers to abnormal glucose tolerance during pregnancy [1]. GDM is potentially harmful to both mother and offspring, including increased amniotic fluid [2], preeclampsia [3], premature birth [4], ketoacidosis [5] and the development of type 2 diabetes mellitus (T2DM) [6] for mother, and abnormalities in intrauterine development [7], neonatal malformations [8], macrosomia [9], neonatal respiratory distress syndrome [10] and neonatal hypoglycemia [11] for offspring. At present, the study mainly focuses on GDM treatment after the middle and late pregnancy.…”
Section: Introductionmentioning
confidence: 99%